Does Green Economy Video Really Work? The Effectiveness of Using Video Content Marketing in Forming MSMEs Perception and Behavior to Implement Green Economy - Rizka Zulfikar; Prihatini Ade Mayvita (University of Islam Malang, 2019)
This study aims to assess the effectiveness of the use of video content marketing in performing SMEs perceptions and behavior in implementing the concept of a green economy. The expected results of this research will make the using of video marketing content can be used as a material consideration for use in socialization and guidance to SMEs about the concept of green economy. This study was conducted in South Kalimantan province with the population, and the sample was SMEs in South Kalimantan province as much as 164 respondents. Researcher use purposive sampling as research method with one group pretest-posttest as research design. The data was collected using interviews and questionnaires. Data analysis technique are descriptive statistics and Wilcoxon Sign Rank Test. This study found that there is an average difference of perception and behavior of respondents about green economy before and after treatment with the video content marketing.